2018
DOI: 10.1371/journal.ppat.1007086
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking of multiple phospholipid biosynthetic pathways and induction of membrane biogenesis by a picornaviral 3CD protein

Abstract: RNA viruses induce specialized membranous structures for use in genome replication. These structures are often referred to as replication organelles (ROs). ROs exhibit distinct lipid composition relative to other cellular membranes. In many picornaviruses, phosphatidylinositol-4-phosphate (PI4P) is a marker of the RO. Studies to date indicate that the viral 3A protein hijacks a PI4 kinase to induce PI4P by a mechanism unrelated to the cellular pathway, which requires Golgi-specific brefeldin A-resistance guani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 81 publications
3
64
0
Order By: Relevance
“…2A ). The differences in outcome could reflect the differences in replication efficiency and/or a direct consequence of the substitutions in 3D-coding sequence on virus assembly or spread caused by changes to 3CD protein or 3D-containing precursor protein (31, 32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A ). The differences in outcome could reflect the differences in replication efficiency and/or a direct consequence of the substitutions in 3D-coding sequence on virus assembly or spread caused by changes to 3CD protein or 3D-containing precursor protein (31, 32).…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for this outcome is that the RdRp is encoded by the 3D region of the viral genome and this region is also a component of the PV 3CD protein. The 3CD protein has well established roles in aspects of the lifecycle before, during, and after replication, including virion morphogenesis (31, 32, 43, 44). Observations such as these highlight the additional level of complexity associated with establishing a cause-and-effect relationship between biochemical properties of the RdRp and fitness, virulence, and/or pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this outcome is that the RdRp is encoded by the 3D region of the viral genome and this region is also a component of the PV 3CD protein. The 3CD protein has well established roles in aspects of the lifecycle before, during, and after replication, including virion morphogenesis [29,42,50,51]. Observations such as these highlight the additional level of complexity associated with establishing a cause-and-effect relationship between biochemical properties of the RdRp and fitness, virulence, and/or pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, growth of each virus was far more distinct than observed for the replicon, with PS-KH PV much slower than IF-KH PV and IF-PS-KH PV was substantially faster than both double mutants ( Figure 2A). The differences in outcome could reflect the differences in replication efficiency and/or a direct consequence of the substitutions in 3D-coding sequence on virus assembly or spread caused by changes to 3CD protein or 3D-containing precursor protein [29,42]. After a productive infection, the exponential phase of genome replication by PV typically occurs between 2 and 6 h post-infection, with virus assembly occurring between 4 and 8 h post-infection.…”
Section: Characterization Of the Double-and Triple-mutant Viruses Andmentioning
confidence: 99%
“…It was further shown that PC was specifically enriched at the sites of BMV replication (25). PC enrichment at the sites of viral replication was also present in HCV-and poliovirus-infected cells, indicating a conserved feature among a group of (ϩ)RNA viruses (25,40). In yeast cells, Cho2p (choline-requiring 2), a phosphatidylethanolamine (PE) methyltransferase (PEMT) that converts PE to monomethyl PE (PMME) (41), is recruited to viral replication sites by an interaction with BMV 1a (25).…”
mentioning
confidence: 93%